A computational study on the adsorption and sensing of gabapentin by pristine and doped B12N12 nanocages - Aydogdu, Seyda (ELSEVIER SCIENCE INC, 2026)
Gabapentin, one of the widely used antiepileptic drugs in the world, is found in aquatic environments because it cannot be completely removed by wastewater treatment techniques. Especially in the recent years, its accumulation in the aquatic environment has caused increasing concerns due to its toxic effects. For this reason, elimination and/or sensing of gabapentin from the water environment is necessitated. In the light of this, this context investigates a suitable nanomaterial by using Density Functional Theory. Within this study, the adsorption performance of XB11N12 (X: B, C, Al, Si, Ga) is evaluated. The interaction of gabapentin with the B12N12 and doped XB11N12 nanocages is analyzed with the help of Natural Bond Orbital Analysis, Quantum Theory of Atoms in Molecules, and Non-Covalent Interaction Analysis. Additionally, the sensing performance of the nanomaterials, and spontaneous behavior of processes are determined. The Electric Field effect on the adsorption and sensing of gabapentin is also inspected. It is found that the adsorption of gabapentin onto the Al doped nanocage is more suitable than the other doped nanocages with its more spontaneous nature. Hence, according to results, external Electric Field has an effect on the adsorption process. The obtained results demonstrate that doping of the B12N12 nanocage may be a promising method for gabapentin removal. It is hoped that the obtained results will be encouraging for new nanomaterials experiments in the future.
Keywords: Adsorption; Density functional Theory; Gabapentin; Nanocage; Sensing; WASTE-WATER TREATMENT; ELECTRONIC-PROPERTIES; ENERGIES; ZEBRAFISH; DRUGS; Biochemistry & Molecular Biology; Computer Science; Crystallography; Mathematical & Computational Biology